Effect of Fungal Bioformulator Concentrate on the Growth and Yield of Corn (Zea mays L.) under Dryland Conditions - Wawan Apzani; Agung Widya Wardhana (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
The urgency of this research lies in the application of bioformulator fungal concentrate as a renewable product with more economical synthesis costs, utilizing the natural potential of surrounding environment to stimulate the growth of corn in dry land. The primary objective of this study is to increase corn production in in Toya Village, Aikmal District, East Lombok, West Nusa Tenggara (NTB), to meet community needs. The research method used is an experimental method with field trials. This study employs a Randomized Complete Block Design (RCBD) with factorial experiment consisting of four levels of BFK and three levels of variety. Each treatment is repeated three times, resulting in a total of 36 experimental units. The data were analyzed using analysis of variance (ANOVA), and if significant differences are found, the Honestly Significant Difference (HSD) was conducted using test at a significance level of 95%. The application of fungal bioformulator concentrate did not show a significant effect in improving the growth and yield of maize in dryland conditions.